Preview: Geomechanics and Tunnelling 5/2016. Issue 4 (August 2016) - Unknown
Abstract: O.K. Wagner, G. Gobiet, H. Druckfeuchter: Semmering Base Tunnel completely under construction – Geotechnical prediction transforms to framework plan / W. Pacher, G. Putz: Semmering Base Tunnel Lot 2.1 Fröschnitzgraben – Custom made solutions for complex shaft structures / J. Benedikt, H. Wagner, T. Herzeg: The St. Kanzian Tunnel Chain – Construction under partly extreme conditions / J. Bauer, B. Kohlböck, B. Moritz, G. Zwittnig: Tunnel chain Granitztal along the Koralm Railway – Interim report of current construction works / P. Sellner, H. Sonnleitner: Motorway Tunnel Gleinalm, 2nd Tube – A logistical challenge / C. Schönlechner, M. Bitschnau: The construction of the Obervermuntwerk II pumped storage plant Geothermal energy – Experiences, chances and risks P. Dumas: A European perspective of the development of deep geothermal in urban areas / J. Hofinger: The contribution of building‐inte grated geothermal systems to the energy transition / A. Csesznák, R. Järschke, M. Wittke: B10 Rosensteintunnel – Designing a geothermal energy system in a spa protection area / C. Moormann, P. Buhmann, N. Pralle, W. Friedermann, S. Homuth: Tunnel geothermics – International experiences with renewable energy concepts in tunnelling projects / S. Lorenz, T. Stoxreiter, R. Galler: Min‐THERM – Utilization of the overburden of existing underground structures for deep geothermal projects / H. Hofstätter, R. Fruhwirt: An innovative approach for optimizing geothermal energy recovery Geomechanical aspects in mining (surface and underground mining) R. Poisel, B. Kolenprat, M. Bertagnoli, M. Ahmadabadi, B. Grasemann, N. Hödlmoser: The rock slide hazard in the former quarry near Spitz and ist foreland / H. Schütz, H. Konietzky: Results of investigations of flooding induced seismicity in the mining district of Schlema/Alberoda, Germany / F. Gaul, S. Eggenreich: The introduction of a microseismic monitoring system in the Mittersill Tungsten Mine and first results / H. Blaha, T. Ladinig, H. Wagner: Design consideration for pillar systems in deep mines / A.R.A. Gomes, E. Roja, J.C. Ulloa, N. Valdez: Geomechanical aspects involved in severe rock damage of undercut and production level pillars of the Esmeralda sector of El Teniente Mine TBM – Expectations and reality J. Klitzen, J. Herdina: Hydroshield drive with a diameter of 13 m in the Lower Inn Valley – Project design and experience from execution of lot H3‐4 / J. Daller, M. Diewald, J. Lemmerer, G. Zwittnig: Expectations and reality at the TBM sections of the Wienerwaldtunnel – Project execution based on partnership / T. Jesel, F. Amberg, T. Rohrer: TBM excavation at the Gotthard Base Tunnel, design and experience from the lot Bodio/Faido / H. Köhler, R. Rengshausen: Metro Doha Greenline – EPB Tunnel drives considering special conditions